DEVELOPMENT OF STUDENTS' COMMUNICATIVE SKILLS IN RUSSIAN LANGUAGE LESSONS - Tojiddinova Mokhlaroy, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract.  The  article  analyzes  the  development  of  students'  communicative competence  in  Russian  language  lessons  as  one  of  the  main  tasks  of  teaching  this subject. Each Russian language lesson, no matter what topic is discussed, should be subordinated to these tasks, taking into account the specifics of the class, the nature of the educational material, and the age characteristics of students.